Changes in spatial patterns of PM2.5 pollution in China 2000–2018: Impact of clean air policies. (August 2020) - Xiao, Qingyang; Geng, Guannan; Liang, Fengchao; Wang, Xin; Lv, Zhuo; Lei, Yu; Huang, Xiaomeng; Zhang, Qiang; Liu, Yang; He, Kebin
Highlights: Satellite-based PM2.5 predictions at 1-km resolution during 2000–2018 were employed. Clean air policies modified PM2.5 spatial patterns and pollution-economic relation. Urban areas showed higher PM2.5 levels and greater PM2.5 reduction than rural areas. Stricter emission control led to greater decline in urban-rural PM2.5 gap after 2013. Abstract: To improve air quality, China has been implementing strict clean air policies since 2013. These policies not only substantially improved air quality but may also modify the spatial distribution of air pollution, since urban emission sources were under stricter control and some were moved to rural regions with lower air quality improvement targets and lacking of monitoring. Here, we predicted satellite-based monthly PM2.5 concentrations during 2000–2018 at a 1-km resolution with complete spatial-temporal coverage to analyze changes in the spatial pattern of PM2.5 pollution in China. We found that the PM2.5 concentration in urban regions was higher than that in rural regions of the same city by an average of 3.3 μg/m 3 during 2000–2018. This urban-rural disparity in PM2.5 concentration significantly increased from 2.5 μg/m 3 in 2000 and peaked in 2007 of 3.8 μg/m 3, then it sharply declined by 49% during 2013–2018 with the implementation of clean air policies. This shrinkage in the urban-rural PM2.5 gap was partly due to the 1.3 μg/m 3 greater average decrease in the PM2.5 level in the urban region than in the rural region of the same town during 2013–2018 on average. We also observed that cities that started monitoring earlier experienced greater decreases in the urban-rural PM2.5 difference, and regions surrounding monitor showed significantly greater PM2.5 decrease than regions far away from monitor during 2013–2018. Additionally, clean air policies modified the relationship between PM2.5 concentrations and per capita gross domestic product (GDP), leading to a lower PM2.5 level with the same per capita GDP after 2013. Emissions in rural and suburban regions should be considered to further improve air quality in China.